Glutathione Transferases Are Involved in the Genotype-Specific Salt-Stress Response of Tomato Plants - Edit Horváth; Kitti Kulman; Bernát Tompa; Ádám Barnabás Hajnal; Alina Pelsőczi; Krisztina Bela; Ágnes Gallé; Jolán Csiszár (MDPI AG, 2023)
Glutathione transferases (GSTs) are one of the most versatile multigenic enzyme superfamilies. In our experiments, the involvement of the genotype-specific induction of GST genes and glutathione- or redox-related genes in pathways regulating salt-stress tolerance was examined in tomato cultivars (Solanum lycopersicum Moneymaker, Mobil, and Elán F1). The growth of the Mobil plants was adversely affected during salt stress (100 mM of NaCl), which might be the result of lowered glutathione and ascorbate levels, a more positive glutathione redox potential (EGSH), and reduced glutathione reductase (GR) and GST activities. In contrast, the Moneymaker and Elán F1 cultivars were able to restore their growth and exhibited higher GR and inducible GST activities, as well as elevated, non-enzymatic antioxidant levels, indicating their enhanced salt tolerance. Furthermore, the expression patterns of GR, selected GST, and transcription factor genes differed significantly among the three cultivars, highlighting the distinct regulatory mechanisms of the tomato genotypes during salt stress. The correlations between EGSH and gene expression data revealed several robust, cultivar-specific associations, underscoring the complexity of the stress response mechanism in tomatoes. Our results support the cultivar-specific roles of distinct GST genes during the salt-stress response, which, along with WRKY3, WRKY72, DREB1, and DREB2, are important players in shaping the redox status and the development of a more efficient stress tolerance in tomatoes.